Systematic procedure for the classification of proven and potential teratogens for use in research. Issue 4 (11th March 2016) - Eltonsy, Sherif; Martin, Brigitte; Ferreira, Ema; Blais, Lucie
Abstract : Background: Although there is strong evidence that some medications are teratogenic, the current lists of teratogens to be used in research are outdated. The objective of this study was to develop an updatable and systematic procedure to the classification of medications proven and potentially teratogenic in the first trimester of pregnancy, for use in research. Methods: We developed a two‐step procedure for teratogen classification. Step 1 includes classifying the medications from Drugs in Pregnancy and Lactation: a Reference Guide to Fetal and Neonatal Risk (9th ed.) into two provisional lists: (1) teratogenic medications, and (2) potentially teratogenic medications. We also searched other references to add other medications. In Step 2, the Teratology Information System (TERIS) database was searched, and the medication was classified as teratogenic or potentially teratogenic according to a newly developed scheme. Expert consensus was used if a medication was not recorded in TERIS. Results: A total of 114 medications were identified in Drugs in Pregnancy and Lactation: a Reference Guide to Fetal and Neonatal Risk, with 57 medications in each provisional list. Seventy‐eight medications were identified in other sources. A total of 135 medications were included in Step 2; the TERIS scheme classified 23 medications, and 112 medications required expert opinion. The two experts agreed on 78.6% of the medications (kappa = 0.63). We identified 91 teratogenic and 81 potentially teratogenic medications. Conclusion: Using reliable references, we established a systematic procedure to the classification of medications with evidence of or potential teratogenic risk. These exhaustive lists will be useful in teratology research and related fields. Birth Defects Research (Part A) 106:285–297, 2016. © 2016 Wiley Periodicals, Inc.